5 years DKMS Chile: approach, results and impact of the first unrelated stem cell donor center in Chile - Barriga, Francisco; Solloch, Ute V.; Giani, Anette; Palma, Julia; Wietstruck, Angélica; Sarmiento, Mauricio; Carvallo, Cristian; Mosso, Claudio; Ramirez, Pablo; Sanchez, Matias; Rojas, Nicolas; Alfaro, Jorge; et al. (Frontiers in Medicine, 2023)
Introduction: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is performed worldwide to treat blood cancer and other life-threatening blood disorders. As successful transplantation requires an HLA-compatible donor, unrelated donor centers and registries have been established worldwide to identify donors for patients without a family match. Ethnic minorities are underrepresented in large donor registries. Matching probabilities are higher when donors and patients share the same ethnic background, making it desirable to increase the diversity of the global donor pool by recruiting donors in new regions. Here, we report the establishment and first five years of operation of the first unrelated stem cell donor center in Chile, a high-income country in South America with a population of over 19 million. Methods: We used online and in-person donor recruitment practices through patient appeals and donor drives in companies, universities, the armed forces, and public services. After confirmatory typing donors were subjected to medical work-up and cleared for donation. Results: We recruited almost 170,000 donors in five years. There were 1488 requests received for confirmatory typing and donor availability checks, of which 333 resulted in medical work-up, leading to 194 stem cell collections. Products were shipped to Chile (48.5%) and abroad. Even when the COVID-19 pandemic challenged our activities, the number of donors recruited and shipped stem cell products remained steady. In Chile there was an almost 8-fold increase in unrelated donor transplantation activity from 16 procedures in 2016-2018 to 124 procedures in 2019-2021, mainly for pediatric patients, following the center's establishment. We estimate that 49.6% of Chilean patients would find at least one matched unrelated donor in the global DKMS donor pool. Discussion: Establishing a DKMS donor center in Chile has significantly increased donor availability for Chilean patients and contributed to an increase of unrelated donor stem cell transplant activity.